NEW SOLUTIONS FOR MAKING ELECTRIC MACHINES WITH HIGH SPECIFIC POWERS FOR PROPULSION SYSTEMS OF ELECTRIC AND HYBRID VEHICLES (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2023)
—
Keywords: electric vehicles; high specific powers; propulsion; electric and hybrid vehicles